Angiopoietin-like 4 directs uptake of dietary fat away from adipose during fasting - Emily M. Cushing; Xun Chi; Kelli L. Sylvers; Shwetha K. Shetty; Matthew J. Potthoff; Brandon S.J. Davies (Elsevier, 2017)
Objective: Angiopoietin-like 4 (ANGPTL4) is a fasting-induced inhibitor of lipoprotein lipase (LPL) and a regulator of plasma triglyceride metabolism. Here, we examined the kinetics of Angptl4 induction and tested the hypothesis that ANGPTL4 functions physiologically to reduce triglyceride delivery to adipose tissue during nutrient deprivation. Methods: Gene expression, LPL activity, and triglyceride uptake were examined in fasted and fed wild-type and Angptl4−/− mice. Results: Angptl4 was strongly induced early in fasting, and this induction was suppressed in mice with access to food during the light cycle. Fasted Angptl4−/− mice manifested increased LPL activity and triglyceride uptake in adipose tissue compared to wild-type mice. Conclusions: Angptl4 is induced early in fasting to divert uptake of fatty acids and triglycerides away from adipose tissues.